Strategies to discover the meaning of unknown words in the english texts of students of the arenillas high school - Suin Romero, Diana Carolina (Machala : Universidad Técnica de Machala, 2016)
This current paper has as objective to implement a proposal which contained suitable teaching and learning strategies to discover the meaning of unknown words contained in the didactic texts of the english language. the learning of a new language is a little difficult at first, but not impossible; however teachers do not provide sufficient motivation and innovative strategies for encourage students to have interest in learning. the acquisition of new vocabulary is the main problem that the students present; because if it is true, the vocabulary that a person has is the basis for learning other skills in english. currently, most students look at english as a subject that only have to approve at any cost without caring if they learned. for this reason, they do not use the learning strategies to help during english classes, and above all, achieve its goal of being able to learn a new language, such as english, a universal language that opens the door to many opportunities of work. the methodology that was used is descriptive, it was sustained on sources that containing scientific journals and articles. also, it was used scientific research methods to support the contextualization of the problem. this was instrumental for the formulation of conclusions, the same that would help to get ideas about strategies that can be followed to discover the meaning of unknown words in the student’s english texts, in this way they will enhance in enriching their vocabulary and perform their exercises in class without any difficulty.
Keywords: STRATEGY; LEARNING; VOCABULARY; ENGLISH; SKILL